A Diversified Study of the Models of Communication and Public Opinion (Global Journal of Human-Social Science, 2012)
This systematic study examines the survey of models was made to study Communication as the necessity of life And if communication is oxygen for an individual and blood for society then channels of communication work as nerves of the society First of all we would discuss Mass Communication and then Public Opinion We have tried to cover different aspects related to the topic Both the portions are interdependent Sources of Mass Communication are the most important means of framing public opinion and media contents are in accordance of public opinion As far as basic structure of mass media as concerned it is adopted from western countries So when we try to impose that theoretical pattern on our sociopolitical- economic set up we find ourselves uncomfortable and incompatible Indian writers are working in this field but still it is in western shades
Keywords: Communication Mass-media; public opinion; socio-political-economic